Peran Sosial Media dalam Meningkatkan Hasil Penjualan Produk Food and Beverage di Hotel Yellow Star Gejayan Yogyakarta - Meyraguchiani, Meyraguchiani; TH, Aletta Dewi Maria (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
This study aims to investigate the influence of social media marketing strategies on the sales of food and beverage products at Hotel Yellow Star Gejayan Yogyakarta. The research method employed was qualitative, using in-depth interviews, participatory observation, document analysis, and observation techniques. The study subjects included marketing managers, social media staff, and hotel consumers.The analysis results indicate that social media marketing strategies are effective in enhancing the sales of food and beverage products at the hotel. Key factors influencing the success of marketing strategies include active interaction with followers, engaging and relevant content, utilizing local influencers, and promptly responding to consumer feedback. Consumers responded positively to social media promotions, reflected in increased product bookings and hotel visits.The conclusion drawn from this research is that social media marketing strategies significantly impact the sales of food and beverage products at Hotel Yellow Star Gejayan Yogyakarta. This highlights the importance of implementing effective and responsive marketing strategies tailored to consumer trends and needs through social media platforms in the hospitality industry context.